The network security test lab : a step-by-step guide - Gregg, Michael (Michael C.) (Indianapolis, IN : Wiley, 2015)
This book sets you up for success defending your company's network against a full complement of today's most-damaging malware, viruses, and other attack technologies. Written to be a practitioner's tool, it will show you how to dissect network packets and gives you reliable strategies for defending against a variety of threats--including network attacks, crimeware, malware, and the most-prevalent malicious traffic--and trains you on the software used by the top experts in the field to implement your unique plan, including Wireshark, Networkminer, Nmap, Metasploit, and more. Step-by-step instruction begins with explaining how to accurately assess your network's security and establish processes to test penetration. Keep your security strong by setting up your own security-testing lab inside where you can simulate attacks in isolation to observe how systems are targeted and to customize better defenses to stop them. --
Building a Hardware and Software Test Platform -- Passive Information Gathering -- Analyzing Network Traffic -- Detecting Live Systems and Analyzing Results -- Enumerating Systems -- Automating Encryption and Tunneling Techniques -- Automated Attack and Penetration Tools -- Securing Wireless Systems -- An Introduction to Malware -- Detecting Intrusions and Analyzing Malware -- Forensic Detection.
Includes index.
Online resource; title from PDF title page (Ebsco, viewed Aug. 17, 2015).
Keywords: Computer security -- Evaluation; Computer networks -- Security measures; COMPUTERS /Networking / Security; COMPUTERS / Security / General; Computer networks -- Security measures; Computer security -- Evaluation; Electronic books; Electronic books